Enhanced mTOR complex 1 signaling attenuates diabetic cardiac injury in OVE26 mice. Issue 11 (30th August 2019) - Xu, Xianmin; Kobayashi, Satoru; Timm, Derek; Huang, Yuan; Zhao, Fengyi; Shou, Weinian; Liang, Qiangrong
Abstract : The protein kinase mechanistic target of rapamycin (mTOR) performs diverse cellular functions through 2 distinct multiprotein complexes, mTOR complex (mTORC)1 and 2. Numerous studies using rapamycin, an mTORC1 inhibitor, have implicated a role for mTORC1 in several types of heart disease. People with diabetes are more susceptible to heart failure. mTORC1 activity is increased in the diabetic heart, but its functional significance remains controversial. To investigate the role of mTORC1 in the diabetic heart, we crossed OVE26 type 1 diabetic mice with transgenic mice expressing a constitutively active mTOR (mTORca) or kinase‐dead mTOR (mTORkd) in the heart. The expression of mTORca or mTORkd affected only mTORC1 but not mTORC2 activities, with corresponding changes in the activities of autophagy, a cellular degradation pathway negatively regulated by mTORC1. Diabetic cardiac damage in OVE26 mice was dramatically reduced by mTORca but exacerbated by mTORkd expression as assessed by changes in cardiac function, oxidative stress, and myocyte apoptosis. These findings demonstrated that the enhanced mTORC1 signaling in the OVE26 diabetic heart was an adaptive response that limited cardiac dysfunction, suggesting that manipulations that enhance mTORC1 activity may reduce diabetic cardiac injury, in sharp contrast to the results previously obtained with rapamycin.—Xu, X., Kobayashi, S., Timm, D., Huang, Y., Zhao, F., Shou, W., Liang, Q. Enhanced mTOR complex 1 signaling attenuates diabetic cardiac injury in OVE26 mice. FASEB J. 33, 12800–12811 (2019). www.fasebj.org